Tuft Cells: A New Player in Hirschsprung's Disease - O'Donnell, Anne Marie; Nakamura, Hiroki; Puri, Prem (European Journal of Pediatric Surgery, 2020)
Introduction “Tuft” cells, also known as brush or caveolated cells, are characteristically fusiform shaped, with a distinct apical “tuft” of microvilli extending into the lumen. Double cortin-like kinase 1 (DCLK1) is a microtubule kinase and is a specific marker of intestinal tuft cells. DCLK1-positive tuft cells have been shown to play a key role in gastrointestinal chemosensation, inflammation, and neurotransmission. DCLK1 and Choline acetyltransferase (ChAT), the enzymes responsible for acetylcholine production, are reported to be coexpressed within the gastrointestinal tract. We designed this study to investigate the hypothesis that DCLK1 gene expression is altered in Hirschsprung's disease (HSCR).Materials and Methods HSCR tissue specimens (n = 6) were collected at the time of pull-through surgery, while control samples were obtained at the time of colostomy closure in patients with imperforate anus (n = 6). Quantitative real-time polymerase chain reaction (qRT-PCR) analysis was undertaken to quantify DCLK1 gene expression, and immunolabeling of DCLK1-positive tuft cells was visualized using confocal microscopy.Results qRT-PCR analysis revealed significant downregulation of the DCLK1 gene in both aganglionic and ganglionic HSCR specimens compared with controls (p < 0.05). Confocal microscopy revealed DCLK1-positive tuft cell expression within the colonic mucosa, with a reduction in expression in both aganglionic and ganglionic HSCR colon compared with controls.Conclusion DCLK1 is significantly downregulated in HSCR colon, suggesting a role for tuft cells in cholinergic neurotransmission of the distal colon. The marked decrease in DCLK1 expression within ganglionic specimens highlights the physiologically abnormal nature of this segment in HSCR patients.
Keywords: tuft cells; double cortin-like kinase 1; Hirschsprung's disease; aganglionosis